2017
DOI: 10.1002/cam4.1202
|View full text |Cite
|
Sign up to set email alerts
|

NLRC and NLRX gene family mRNA expression and prognostic value in hepatocellular carcinoma

Abstract: Nucleotide‐binding oligomerization domain (NOD)‐like receptor (NLR)C and NLRX family proteins play a key role in the innate immune response. The relationship between these proteins and hepatocellular carcinoma (HCC) remains unclear. This study investigated the prognostic significance of NLRC and NLRX family protein levels in HCC patients. Data from 360 HCC patients in The Cancer Genome Atlas database and 231 patients in the Gene Expression Omnibus database were analyzed. Kaplan–Meier analysis and a Cox regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 66 publications
(77 reference statements)
1
8
0
Order By: Relevance
“…The NOD-like receptor signaling pathway is composed of regulating factors and receptors including NLRC and NLRX family gene members. This result parallels our previous report that NLRC and NLRX gene subfamily members are potential biomarkers for HCC 56. Hepatitis B was enriched in the results by targeting APAF1 , TICAM1 and TBK1 .…”
Section: Discussionsupporting
confidence: 90%
“…The NOD-like receptor signaling pathway is composed of regulating factors and receptors including NLRC and NLRX family gene members. This result parallels our previous report that NLRC and NLRX gene subfamily members are potential biomarkers for HCC 56. Hepatitis B was enriched in the results by targeting APAF1 , TICAM1 and TBK1 .…”
Section: Discussionsupporting
confidence: 90%
“…By contrast, NLRC4 expression was found to show no correlation with the survival of patients with hepatocellular carcinoma by Wang et al . 33 . Recently, Xiao-Feng et al .…”
Section: Discussionmentioning
confidence: 99%
“…Reduced mRNA levels of NLRC4 are evident in the tumor tissues of colorectal cancer 118 . However, more recent studies have demonstrated normal levels in lung tumors 119 and hepatocellular carcinoma, 120 along with increased expression in breast cancer and glioma 121,122 . The role of NLRC4 in tumor regulation and suppression is not always consistent even in the same tumor model (Table 4), as discussed further below.…”
Section: Nlrc4 In Cancermentioning
confidence: 96%